Cognitive and Surgical Outcome in Mesial Temporal Lobe Epilepsy Associated with Hippocampal Sclerosis Plus Neurocysticercosis: A Cohort Study - Bianchin, Marino M.; Velasco, Tonicarlo R.; Coimbra, Erica R.; Gargaro, Ana C.; Escorsi-Rosset, Sara R.; Wichert-Ana, Lauro; Terra, Vera C.; Alexandre, Jr, Veriano; Araujo, Jr, David; dos Santos, Antonio Carlos; Fernandes, Regina M. F.; Assirati, Jr, João A.; et al. (PLOS ONE, 2013)
Background Where neurocysticercosis (NCC) is endemic, chronic calcified neurocysticercosis (cNCC) can be observed in patients with mesial temporal lobe epilepsy associated with hippocampal sclerosis (MTLE-HS). Considering that both disorders cause recurrent seizures or cognitive impairment, we evaluated if temporal lobectomy is cognitively safe and effective for seizure control in MTLE-HS plus cNCC. Methods Retrospective cohort study of neuropsychological profile and surgical outcome of 324 MTLE-HS patients submitted to temporal lobectomy, comparing the results according to the presence or absence of cNCC. Findings cNCC occurred in 126 (38.9%) of our MTLE-HS patients, a frequency higher than expected, more frequently in women than in men (O.R. = 1.66; 95% C.I. = 1.05–2.61; p = 0.03). Left-side (but not right side) surgery caused impairment in selected neuropsychological tests, but this impairment was not accentuated by the presence of cNCC. Ninety-four (74.6%) patients with MTLE-HS plus cNCC and 153 patients (77.3%) with MTLE-HS alone were Engel class I after surgery (O.R. = 1.16; 95% C.I. = 0.69–1.95; p = 0.58). However, the chances of Engel class IA were significantly lower in MTLE-HS plus cNCC than in patients with MTLE-HS alone (31.7% versus 48.5%; O.R. = 2.02; 95% C.I. = 1.27–3.23; p = 0.003). Patients with MTLE-HS plus cNCC showed higher rates of Engel class ID (15.1% versus 6.6%; O.R. = 2.50; 95% C.I. = 1.20–5.32; p = 0.012). Interpretation cNCC can be highly prevalent among MTLE-HS patients living in areas where neurocysticercosis is endemic, suggesting a cause-effect relationship between the two diseases. cNCC does not add further risk for cognitive decline after surgery in MTLE-HS patients. The rates of Engel class I outcome were very similar for the two groups; however, MTLE-HS plus cNCC patients achieved Engel IA status less frequently, and Engel ID status more frequently. Temporal lobectomy can be safely performed in most patients with MTLE-HS plus cNCC without affecting cognitive outcome. Long-term surgical seizure control in MTLE-HS plus cNCC is still satisfactory, as long as selected patients remain under medication.